2017
DOI: 10.2139/ssrn.2999317
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Market Timing in the Mutual Fund Industry

Abstract: This study complements the scarce literature on conditional market timing in the mutual fund industry by assessing determinants of market timing throughout the distribution of market exposure. It builds on the intuition that the degree of responsiveness by fund managers to The findings broadly suggest that blanket responses of market exposures to investigated factors are unlikely to represent feasible strategies for fund managers unless they are contingent on initial levels of market exposure and tailored diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In line with the motivation of the study which is to assess the relationship between renewable energy and CO 2 emissions throughout the conditional distributions of CO 2 emissions, this study adopts the quantile regression strategy. As discussed in the introduction, previous assessments of the underlying nexus such as the by Nathaniel and Iheonu (2019) In the light of the above, this study builds on the attendant quantile regressions (QR) literature (Koenker & Bassett, 1978;Tchamyou & Asongu, 2018) which has been documented to be appropriate in articulating initial levels of the outcome variables (Okada & Samreth, 2012;Asongu, 2013). Furthermore, as argued by Koenker (2005) and Hao and Naiman (2007), the QR technique is distinct from linear estimations from a multitude of standpoints, inter alia, it: (i) predicts conditional quantiles (compared to conditional mean); is relevant when sufficient data is used (against a baseline Ordinary…”
Section: Methodsmentioning
confidence: 99%
“…In line with the motivation of the study which is to assess the relationship between renewable energy and CO 2 emissions throughout the conditional distributions of CO 2 emissions, this study adopts the quantile regression strategy. As discussed in the introduction, previous assessments of the underlying nexus such as the by Nathaniel and Iheonu (2019) In the light of the above, this study builds on the attendant quantile regressions (QR) literature (Koenker & Bassett, 1978;Tchamyou & Asongu, 2018) which has been documented to be appropriate in articulating initial levels of the outcome variables (Okada & Samreth, 2012;Asongu, 2013). Furthermore, as argued by Koenker (2005) and Hao and Naiman (2007), the QR technique is distinct from linear estimations from a multitude of standpoints, inter alia, it: (i) predicts conditional quantiles (compared to conditional mean); is relevant when sufficient data is used (against a baseline Ordinary…”
Section: Methodsmentioning
confidence: 99%
“…First, the bulk of African business literature is consistent with the position that a fundamental challenge to doing business on the continent is the lack of finance (Allen, Otchere, & Senbet, ; Daniel, ; Darley, ; Fanta, ; Fowowe, ; Iyke & Odhiambo, ; Obeng & Sakyi, ; Osah & Kyobe, ; Tchamyou & Asongu, ; Tuomi, ). This position has recently been confirmed by Ndikumana and Blackson (), who have shown that domestic investment in Africa is more positively linked to domestic sources of capital when compared with external sources of capital.…”
Section: Introductionmentioning
confidence: 97%
“…In order to control for existing levels of financial efficiency in the investigation of the complementarity between ISM and mobile phones on financial efficiency, we employ quantile regressions (hereafter, QR). As noted by Keonker and Hallock (2001) and Tchamyou and Asongu (2017b), its application in conditional development literature has consisted of investigating the determinants of financial allocation efficiency throughout the conditional distributions of financial allocation efficiency.…”
Section: Methodsmentioning
confidence: 99%